Graduate Psychology Education in National University of La Plata (Argentina) and the Role of Scientific Journals, 1976-2000 - González, Eliana Noemí; UNSL / CONICET (Pontificia Universidad Javeriana, 2015)
This work is at the intersection of two lines of historical research: a psychology education history and a scientific journal history. It is attemped to analyze the teaching of Psychology at the National University of La Plata (UNLP), during the period 1976-2000. A first description of it is outlined by making use of a socio-bibliometrical analysis of the references at the syllabus of the courses taught at the Program of Psychology at the UNLP in such a period. The incidence of the journals referenced at the syllabus is quantitatively and qualitatively analyzed to highlight their incidence in the contents taught.